Analysis of the Determinants of Open Unemployment and Poverty Rates in East Java Province - Natasya Nur Fadila; Kukuh Arisetyawan (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2026)
The purpose of this study is to analyze the simultaneous and partial influences of the labor force participation rate, human development index, district/city minimum wage, per capita expenditure, and technology on the open rate and poverty in the regencies/cities of East Java Province for the period 2020-2024. Using a quantitative approach with multivariate analysis and multiple and simple regression. Data obtained from the Central Statistics Agency. The results show that the labor force participation rate, human development index, district/city minimum wage, per capita expenditure, and technology simultaneously influence the open unemployment rate, which ultimately also affects poverty in the regencies/cities of East Java Province.